Recent ground thermo-hydrological changes in a southern Tibetan endorheic catchment and implications for lake level changes ... - Martin, Léo C. P.; Westermann, Sebastian; Magni, Michele; Brun, Fanny; Fiddes, Joel; Lei, Yanbin; Kraaijenbrink, Philip; Mathys, Tamara; Langer, Moritz; Allen, Simon; Immerzeel, Walter (Humboldt-Universität zu Berlin, 2023)
Climate change modifies the water and energy fluxes between the atmosphere and the surface in mountainous regions such as the Qinghai–Tibet Plateau (QTP), which has shown substantial hydrological changes over the last decades, including rapid lake level variations. The ground across the QTP hosts either permafrost or is seasonally frozen, and, in this environment, the ground thermal regime influences liquid water availability, evaporation and runoff. Consequently, climate-induced changes in the ground thermal regime may contribute to variations in lake levels, but the validity of this hypothesis has yet to be established. This study focuses on the cryo-hydrology of the catchment of Lake Paiku (southern Tibet) for the 1980–2019 period. We process ERA5 data with downscaling and clustering tools (TopoSCALE, TopoSUB) to account for the spatial variability of the climate in our forcing data (Fiddes and Gruber, 2012, 2014). We use a distributed setup of the CryoGrid community model (version 1.0) to quantify ...